Sporotrichosis: an emerging neglected opportunistic infection in HIV-infected patients in Rio de Janeiro, Brazil. - Dayvison Francis Saraiva Freitas; Antonio Carlos Francesconi do Valle; Margarete Bernardo Tavares da Silva; Dayse Pereira Campos; Marcelo Rosandiski Lyra; Rogerio Valls de Souza; Valdiléa Gonçalves Veloso; Rosely Maria Zancopé-Oliveira; Francisco Inácio Bastos; Maria Clara Gutierrez Galhardo (Public Library of Science (PLoS), 2014)
Sporotrichosis associated with zoonotic transmission remains a relevant public health problem in Rio de Janeiro, Brazil, affecting a large at-risk population, which includes HIV-infected individuals. We assessed patients co-infected by Sporothrix spp. and HIV over time in the context of an unabated sporotrichosis epidemic. A retrospective cohort retrieved information from a National reference institute for infectious diseases regarding 48 patients with sporotrichosis-HIV co-infection (group 1) as well as 3,570 patients with sporotrichosis (group 2), from 1987 through March 2013. Most patients from group 1 were male (68.8%), whereas women were predominant in group 2 (69.1%; p<0.0001). Patients from group 1 were younger than those from group 2 (μ = 38.38±10.17 vs. 46.34±15.85; p<0.001) and differed from group 2 in terms of their race/ethnic background, with 70.8% non-white patients in group 1 vs. 38.6% from group 2 (p<0.0001). Close to half (∼44%) of the patients from group 1 were hospitalized due to sporotrichosis over time, whereas hospitalization was very unlikely in group 2, among whom approximately 1% were hospitalized over time. Dissemination of sporotrichosis was the main cause of hospitalization in both groups, although it was more common among hospitalized patients from group 1 (19/21 [90.5%] vs. 16/37 [43.2%]; p<0.001). Over the period under analysis, eight patients died due to sporotrichosis (3/48 vs. 5/3,570). The diagnosis of sporotrichosis elicited HIV testing and subsequent diagnosis in 19/48 patients, whereas 23/48 patients were simultaneously diagnosed with the two infections. HIV infection aggravates sporotrichosis, with a higher incidence of severe disseminated cases and a higher number of hospitalizations and deaths. Underserved populations, among whom sporotrichosis has been propagated, have been affected by different transmissible (e.g., HIV) and non-transmissible diseases. These populations should be targeted by community development programs and entitled to integrated management and care of their superimposed burdens.